2016
DOI: 10.1016/j.scitotenv.2016.08.160
|View full text |Cite
|
Sign up to set email alerts
|

Sediment characteristics and microbiological contamination of beach sand – A case–study in the archipelago of Madeira

Abstract: Beach sand can harbour pathogenic and opportunistic microorganisms, as well as faecal indicator bacteria that influence directly the bathing water quality. Pathogenic and opportunistic microorganisms often raise concern of exposure during beach related recreational activities. In this work, three different types of sandy beaches (natural basaltic, natural calcareous and artificial calcareous) of the Archipelago of Madeira (Portugal) were sampled for bacterial and fungal contaminants and grain size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
1
18
0
2
Order By: Relevance
“…30,31 We could not detect the presence of dermatophytes in the Israeli beach sands, which possibly might be due to the high temperature of the sands. The presence of dermatophytes was reported rather scarcely in the literature, 32,33 and might be associated with specific ecological conditions, such as those found on the Madeira archipelago. 32 Sabino et al 33 faster, more accurate and can be performed by non-experts in the field of fungal morphology.…”
Section: F I G U R Ementioning
confidence: 99%
“…30,31 We could not detect the presence of dermatophytes in the Israeli beach sands, which possibly might be due to the high temperature of the sands. The presence of dermatophytes was reported rather scarcely in the literature, 32,33 and might be associated with specific ecological conditions, such as those found on the Madeira archipelago. 32 Sabino et al 33 faster, more accurate and can be performed by non-experts in the field of fungal morphology.…”
Section: F I G U R Ementioning
confidence: 99%
“…Similarly, at a beach that underwent renovation, replacing calcium carbonate dominated sand with quartz sand (Hernandez et al 2014), substantial decreases were observed in FIB levels in both the sand and adjacent surface water, suggesting that calcium carbonate particles retain EPS and FIB more readily in comparison to quartz. However, other cases have reported that mineralogy may not influence FIB releases from sand, such as is the case reported by Abreu et al (2016) for beaches in Madeira, Portugal.…”
Section: Hangouts: Biofilms and Other Reservoirs Of Fecal Microorganismsmentioning
confidence: 76%
“…Similarly, Yamahara et al (2007) found that sheltered beaches in California had higher FIB than open ocean beaches with higher wave energy. Abreu et al (2016) observed higher microbial loading at beaches with artificial infrastructure designed to embay and protect them in the Madeira Archipelago. The amount of biofilm on sand particles, as measured by EPS levels, appears to be related to wave energy (Piggot et al 2012).…”
Section: Hangouts: Biofilms and Other Reservoirs Of Fecal Microorganismsmentioning
confidence: 88%
See 2 more Smart Citations